GABAA receptors as plausible molecular targets and mediators for taurine and homotaurine actions - Meera, Pratap; Uusi-Oukari, Mikko; Lipshutz, Gerald S.; Wallner, Martin (Frontiers in Pharmacology, 2023)
Dementia and autoimmune diseases are prevalent conditions with limited treatment options. Taurine and homotaurine (HT) are naturally occurring sulfonate amino acids, with taurine being highly abundant in animal tissues, but declining with age in the blood. HT is a blood-brain barrier permeable drug under investigation for Alzheimer’s disease. HT also has beneficial effects in a mouse model of multiple sclerosis likely through an anti-inflammatory mechanism mediated by GABAA receptor (GABAAR) agonism in immune cells. While both taurine and HT are structural GABA analogs and thought to be GABA mimetics at GABAARs, there is uncertainty concerning their potency as GABA mimetics on native GABAARs. We show that HT is a very potent GABA mimetic, as it evokes GABAAR-mediated currents with an EC50 of 0.4 μM (vs. 3.7 μM for GABA and 116 µM for taurine) in murine cerebellar granule cells in brain slices with both taurine and HT have similar efficacy in activating native GABAARs. Furthermore, HT displaces the high affinity GABAAR ligand [3H]muscimol at similarly low concentrations (HT IC50 of 0.16 μM vs. 125 μM for taurine) in mouse brain homogenates. The potency of taurine and HT as GABAAR agonists aligns with endogenous concentrations of taurine in the blood and with HT concentrations achieved in the brain following oral administration of HT or the HT pro-drug ALZ-801.Consequently, we discuss that GABAARs subtypes are plausible targets for mediating the potential beneficial effects of taurine in health and life-span extension and the beneficial HT effects in dementia and autoimmune conditions.